Nutritional and Health Benefits of Donkey Milk - Bhairav Prasad (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2020)
Donkey/ass/jenny milk is the milk that is produced by female donkey (Equus asinus) Due to small udder size the quantity produced is very less hence difficult to commercialize. It has been used since ancient times for infant nutrition as well as cosmetic purposes. In the late 20th century the donkey milk was used to feed orphaned infants and cure weak and sick children due to its resemblance with the human breast milk. Due to exceptionally high proximity with human breast milk the donkey are domesticated in Greece, Italy, Belgium, Germany, Switzerland and some other parts of European world. The donkey milk composition shows resemblance to human breast milk for lactose, protein and ash when compared with goat, sheep, cow and camel milk. Several scientific study has proven that the donkey milk contain several active ingredients that boost the immunity and other health benefits. Among functional the donkey milk contains active antimicrobial substance such as lysozyme and lactoferrin. These molecules are also present in goat, sheep and cow milk but in less quantity. The donkey milk also contains less fat and cholesterol than cow, goat and sheep milk. Therefore this milk is best for the cardiovascular or heart patients.